1999
DOI: 10.1021/ma990645n
|View full text |Cite
|
Sign up to set email alerts
|

A New Class of Biodegradable Thermosensitive Polymers. 2. Hydrolytic Properties and Salt Effect on the Lower Critical Solution Temperature of Poly(organophosphazenes) with Methoxypoly(ethylene glycol) and Amino Acid Esters as Side Groups

Abstract: The hydrolytic properties of the novel biodegradable thermosensitive poly(organophosphazenes) with methoxypoly(ethylene glycol) (MPEG) and amino acid esters as side groups have been studied by means of gel permeation chromatography and 31 P and 1 H NMR spectroscopy and by identification of the hydrolysis products. The polymers substituted with R-amino acid esters were hydrolyzed faster than that with β-amino acid ester. The higher content of the amino acid ester in the polymer backbone caused enhanced hydrolys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
100
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(109 citation statements)
references
References 25 publications
8
100
0
Order By: Relevance
“…From the comparative data of three anions, the effectiveness order from 'saltingout' to 'salting-in' in this system is summarized as follows: KCl ≈ KSCN > KBr > KNO 3 > KI. The experiment result is consistent with the investigation on the other polymer system [25]. In overall, 3 , however, appears to be a weak LCST-shifter in our system, which is not in accordance with the study on hydroxypropyl cellulose system by Oshima [24].…”
Section: Effect Of the Additive Salt On Lcst Of The Copolymersupporting
confidence: 75%
“…From the comparative data of three anions, the effectiveness order from 'saltingout' to 'salting-in' in this system is summarized as follows: KCl ≈ KSCN > KBr > KNO 3 > KI. The experiment result is consistent with the investigation on the other polymer system [25]. In overall, 3 , however, appears to be a weak LCST-shifter in our system, which is not in accordance with the study on hydroxypropyl cellulose system by Oshima [24].…”
Section: Effect Of the Additive Salt On Lcst Of The Copolymersupporting
confidence: 75%
“…[5][6][7] There have been extensive efforts to construct biodegradable stimuli-responsive polymers. Several systems based on degradable polyesters, [8][9][10] poly(amino ester)s, [11][12][13] poly(organo phosphazenes), 14 and poly(amino acid)s have been investigated. Among them, polypeptides made from a-amino acid carboxyanhydrides (NCAs) have received extensive research interest for their promising applications.…”
mentioning
confidence: 99%
“…Consequently, the structure and composition of the side groups of the polymers exhibited negligible effects on the ∆LCST obtained by the addition of saccharides. In contrast, inorganic and organic salts 15 showed sensitive effects on the ∆LCST of the present polymers depending on their structures. From such results, it may be concluded that the saccharide effect on the LCST of the thermosensitive poly(organophosphazenes) is affected by saccharide structure rather than by the polymer structure.…”
Section: Resultsmentioning
confidence: 74%
“…14 We have also studied the salt effect on these polymers in aqueous solutions. 15 In this study, saccharide effects on the LCST of poly-(organophosphazenes) were investigated in detail employing several structurally different saccharides.…”
Section: Introductionmentioning
confidence: 99%